2023
DOI: 10.3390/ph16020282
|View full text |Cite
|
Sign up to set email alerts
|

Altered Membrane Expression and Function of CD11b Play a Role in the Immunosuppressive Effects of Morphine on Macrophages at the Nanomolar Level

Abstract: Morphine, one of the most efficacious analgesics, is effective in severe pain, especially in patients with concomitant painful cancers. The clinical use of morphine may be accompanied by increased immunosuppression, susceptibility to infection and postoperative tumor metastatic recurrence, and the specific mechanisms and clinical strategies to alleviate this suppression remain to be investigated. Expression of CD11b is closely associated with the macrophage phagocytosis of xenobiotic particles, bacteria or tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…DRG cultures were prepared from whole DRGs not cleared of non-neuronal cells. While it has been reported that these cells express MOR and can act indirectly to contribute to sensitization of DRG neurons 44 , 45 by an activated of immune response, in vivo 46 48 However, we prepared low-density DRG neuronal cultures that were used within 3 days, at which time there is minimal growth of non-neuronal cells and nociceptor neurites. This approach has allowed us to patch nociceptors without neighboring non-neuronal cells within > 100 µm.…”
Section: Discussionmentioning
confidence: 99%
“…DRG cultures were prepared from whole DRGs not cleared of non-neuronal cells. While it has been reported that these cells express MOR and can act indirectly to contribute to sensitization of DRG neurons 44 , 45 by an activated of immune response, in vivo 46 48 However, we prepared low-density DRG neuronal cultures that were used within 3 days, at which time there is minimal growth of non-neuronal cells and nociceptor neurites. This approach has allowed us to patch nociceptors without neighboring non-neuronal cells within > 100 µm.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of the cannabinoid receptor gene expression in the tramadol-treated group suggests that this opioid alters the signaling of the active zone in the presynaptic terminals, consequently affecting synaptic plasticity and reducing neurotransmitter release probability. The expression of the gene encoding for CD11b, a microglia biomarker, is associated with leukocyte adhesion and inflammatory cell migration [ 103 ]. As a decrease in the expression of the CD11b-encoding gene was observed in both opioid-treated groups, an immunosuppressive effect might be deduced for tramadol and tapentadol, particularly affecting macrophage-induced phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the compounds were tested for their effect on CD11b and CD80 expression in THP-1 cells co-cultured with HT-29. While the effect on CD80 expression was very mild (less than 10% of inhibition rates), all of the compounds tested were found to significantly reduce CD11b expression, which is a promising target for immunomodulation in anticancer therapies [ 23 , 24 ]. In most of the cases, this effect was even higher than the one observed for the reference compound BMS-8.…”
Section: Discussionmentioning
confidence: 99%